Análisis del sistema informático de la Ferretería Electroferro del cantón Ventanas - Borja Arrobo, Kimberly Fernanda (2021)
This case study was carried out at the Electroferro hardware store in the city of Windows and it was an analysis of the computer system, reviewing how its operation is constituted and how it has helped the company in its management of information. It was carried out through a field investigation, and the instruments used were the interview and direct observation, which allowed us to know the correct information for the final analysis. The Onsystec accounting system was also analyzed; briefly, the operation of the main modules used by the company to control the company's electrical and electronic products was observed. In addition, the management and preparation of the personnel was observed to use this system and be able to get the most out of it.